Na corda bamba: trabalho e educação entre o precariado - Mauricio, Francisco Raphael Cruz (2015)
This dissertation deals with the labor and educational experiences of the contemporary precariat seeking to understand the meanings attributed by him to work and education. The social segment of the precariat is formed by young adults who have high schooling and are inserted precariously in work and social life. They make up the "generation of the diploma", formed by the subjects that entered higher education, but that did not necessarily have reverted in salary gains the several years of study. This segment of workers with high schooling experienced the phenomenon of the “deterioration of the chances of insertion of the more educated”. His work and life trajectories are marked by the configuration of the new and fluid world of work, where the elements of uncertainty, insecurity and instability affect the construction of life projects. Having as a methodological contribution the comprehensive interview to reconstruct the precarious work trajectories, I seek to problematize the meanings of the work and in subjects where the academic formation tends to generate positive expectation of insertion in the labor market. In order to analyze my reflections analytically, I carry out, as a theoretical archeology, an analysis of the categories of precarization, precarity and precariat. Then, through the content analysis of interviews, I try to identify the generational and educational profile of the precariat, to understand their living conditions, to trace their paths in the labor market and to understand their ways of being in the world. The work in the precariat now indicates the meanings of project construction, sometimes denotes the meanings of risk. The work proves to be a tightrope where the precariat tries to balance himself between heaven and the hell of social life. The "tightrope" in which the precarious moves after the completion of undergraduate studies is always intended in an attempt to balance education, work and life project. Although we live in a modernity marked by instability, insecurity and uncertainty (BAUMAN, 2001), where capital values the flexibility of men and things (SENNETT, 2012), the precarious value the character of stability and security in a world adverse to these elements. The precarious is a kind of "tightrope" who hangs "battles" to stay on the "tightrope" of life.